Microsomal PGE2 synthase‐1 regulates melanoma cell survival and associates with melanoma disease progression. (15th March 2016) - Kim, Sun‐Hee; Hashimoto, Yuuri; Cho, Sung‐Nam; Roszik, Jason; Milton, Denái R.; Dal, Fulya; Kim, Sangwon F.; Menter, David G.; Yang, Peiying; Ekmekcioglu, Suhendan; Grimm, Elizabeth A.
Summary: COX‐2 and its product PGE2 enhance carcinogenesis and tumor progression, which has been previously reported in melanoma. As most COX inhibitors cause much toxicity, the downstream microsomal PGE2 synthase‐1 (mPGES1) is a consideration for targeting. Human melanoma TMAs were employed for testing mPGES1 protein staining intensity and percentage levels, and both increased with clinical stage; employing a different Stage III TMA, mPGES1 intensity (not percentage) associated with reduced patient survival. Our results further show that iNOS was also highly expressed in melanoma tissues with high mPGES1 levels, and iNOS‐mediated NO promoted mPGES1 expression and PGE2 production. An mPGES1‐specific inhibitor (CAY10526) as well as siRNA attenuated cell survival and increased apoptosis. CAY10526 significantly suppressed tumor growth and increased apoptosis in melanoma xenografts. Our findings support the value of a prognostic and predictive role for mPGES1, and suggest targeting this molecule in the PGE2 pathway as another avenue toward improving melanoma therapy.